Insufficient Balance Recovery Following Unannounced External Perturbations in Persons With Stroke. (September 2019) - Handelzalts, Shirley; Steinberg-Henn, Flavia; Levy, Sigal; Shani, Guy; Soroker, Nachum; Melzer, Itshak
Background . Persons with stroke (PwS) are at increased risk of falls, especially toward the paretic side, increasing the probability of a hip fracture. The ability to recover from unexpected loss of balance is a critical factor in fall prevention. Objectives . We aimed to compare reactive balance capacity and step kinematics between PwS and healthy controls. Methods . Thirty subacute PwS and 15 healthy controls were exposed to forward, backward, right, and left unannounced surface translations in 6 increasing intensities while standing. Single step threshold, multiple step threshold, and fall threshold (ie, perturbation intensity leading to a fall into harness system) were recorded as well as reactive step initiation time, step length, and step velocity. Results . Twenty-five PwS fell into harness system during the experiment while healthy controls did not fall. Fourteen out of 31 falls occurred in response to surface translations toward the nonparetic side, that is, falling toward the paretic side. Compared with healthy controls, PwS demonstrated significantly lower fall threshold and multiple step threshold in response to forward, backward, and lateral surface translations. Impairments were more pronounced in response to forward surface translation and toward the nonparetic side (ie, loss of balance toward the paretic side). A trend toward significant shorter step length in response to lateral surface translations was found in PwS compared with healthy controls. Conclusions . Findings highlight the importance of assessing reactive balance capacity in response to perturbations in different directions and intensities in addition to the routine assessment in PwS.